Evaluation of Tanzania Dairy Development Forum - Cadilhon, Jean Joseph; Kago, Kennedy; Omore, Amos; Katjiuongua, Hikuepi; Mtimet, Nadhem; Bahta, Sirak; Fadiga, Mohamadou; Wanyoike, Francis; Iheanacho, Okike (International Livestock Research Institute, 2015)
Data gathering using methods and tools for value-chain analysis, and analysis of the impact of the Tanzania Dairy Development Forum's structure on the conduct of its members and on achieving their dairy development objectives (impact of upgrading value-chains).